Leading beyond crisis : the five pillars of transformative resilient leadership - Everly, George S., Jr., 1950-; Athey, Amy B. (Ascent Audio, 2023)
It's hard enough to lead in good times. It's even harder to lead in a crisis. This book teaches the art and science of transformative resilient leadership, a unique leadership style that focuses on spotting the opportunities that emerge from times of adversity, and leverages them to foster resilience and growth. With over seventy years of combined experience training leaders in business, military, sports, and other high-pressure settings, psychologists George S. Everly, Jr., and Amy B. Athey have garnered unparalleled insight into how the best leaders navigate the worst. This book distills their wisdom into practical, accessible chapters and profiles leaders from classical and modern history who demonstrate the five pillars of transformative resilient leadership. Whether you are a CEO, frontline manager, director, teacher, coach, or other leader, you can learn to seize the unique opportunities afforded by crisis to achieve organizational, community, and personal growth.